Oyster aquaculture cages provide fish habitat similar to natural structure with minimal differences based on farm location - Mercaldo-Allen, Renee; Auster, Peter J.; Clark, Paul; Dixon, Mark S.; Estela, Erick; Liu, Yuan; Milke, Lisa; Phillips, Gillian; Redman, Dylan; Smith, Barry C.; Verkade, Alison; Rose, Julie M. (Frontiers in Marine Science, 2023)
Oyster aquaculture gear may augment natural seafloor by providing structured habitat for economically important fish species. Underwater video census was used to assess fish abundance and community composition on eastern oyster (Crassostrea virginica) shelf and bag style aquaculture off-bottom cages and within natural rock reef habitat. During 2018, underwater cameras were mounted on four study cages at a dense shellfish farm of 40-100 commercial cages (dense cage farm), on four single cages interspersed on low relief seafloor (sparse cage farm), and amongst four boulders on a rock reef (rock reef), near Milford, Connecticut. In 2019, cameras were similarly deployed on two study cages per farm at each of three shellfish farms off Milford, Norwalk and Westport, CT. Video was recorded hourly in eight-minute segments from 7 am to 7 pm. Data loggers monitored seawater temperature, light intensity, and current speed. Fish abundance (MaxN) was calculated for all videos. We compared fish abundance and community composition between May to September, on cage and boulder habitat, on cages at dense and sparse farms and on cages across farm locations. In 2018, abundance of black sea bass (Centropristis striata), scup (Stenotomus chrysops) and tautog (Tautoga onitis) was significantly higher on cages than boulders, regardless of cage number. Cunner (Tautogolabrus adspersus) abundance was significantly higher on boulders than cages when cage sites were grouped. However pairwise comparisons indicated that cunner were significantly higher at the sparse farm versus the rock reef but cunner abundance on the dense farm and rock reef was not significantly different. Abundance of black sea bass, scup, tautog, and cunner were not significantly different across 2019 farm locations. Young-of-the-year fish occurred episodically at all sites during both years, with black sea bass and scup most abundant. Fish abundance corresponded to seasonal changes in seawater temperature and was highest at the warmest temperatures. Light intensity and current speed explained less variation in fish abundance relative to temperature, and relationships were inconsistent across habitats and farm locations. Our results suggest that multi-tiered oyster aquaculture cages contribute structure to seafloor environments that provide habitat for temperate reef fish similar to natural rock reefs.